Instrumen Penilaian Diri Siswa Untuk Mengukur Sikap Dan Aktivitas Siswa Saat Pembelajaran Daring Biologi - Fajar Adinugraha; Lita Inneka; Marina Silalahi (JURNAL PENDIDIKAN ROKANIA, 2022)
The purpose of the research in this article is to develop a student self-assessment instrument in learning biology. In addition, to determine the correlation of the results of the assessment conducted by the teacher and self-assessment by students. The method used is Research and Development (R & D) with a trial class, namely XI MIPA 2 SMA N 103 Jakarta. The Self-Assessment Instrument for Measuring Student Attitudes and Activities consists of (A) Cover, (B) Introduction Page, Table of Contents, and Guide Information, (C) Introduction, (D) Questions and Answer Sheets, (E) Score Calculations, (F) Closing and Bibliography. The questions consist of 19 questions using a rating scale with indicators: Spiritual Attitude, Honesty, Discipline, Responsibility, Tolerance, Environmental Care, Curiosity Attitude, Critical Thinking Attitude, Perseverance, Thoroughness, Cooperation, Creativity, Observing, Interpreting and Associating, Asking a question, Formulating tentative hypotheses or conjectures, Using tools and materials/performing scientific activities, Applying concepts, and Communicating. Based on the Spearman Rank Correlation Test, there is no match (correlation) between raters X (students) and raters Y (teachers). However, students stated that it was effective as a form of self-reflection